Identifikasi dan Predileksi Ektoparasit Kepiting Bakau (Scylla spp.) dari Ekosistem Mangrove Taman Hutan Raya (TAHURA) Ngurah Rai, Bali - Muttaqin, Ilham; Julyantoro, Pande Gde Sasmita; Sari, Alfi Hermawati Waskita (Current Trends in Aquatic Science, 2018)
This research aims to know the various types, predilections, prevalence and intensity of ectoparasites on mud crab (Scylla spp.) and water quality condition in Taman Hutan Raya (TAHURA) Ngurah Rai, Bali. This research was conducted in TAHURA mangrove ecosystem which has 219 hectare of research area near to Pemogan village from February to April 2018. The research used descriptive method by using random sampling for collecting data. Mud crabs obtained in this research consisted of 21 individual mud crabs that belong to 3 species, namely Scylla olivacea (11 ind), Scylla serrata (9 ind), and Scylla tranquebarica (1 ind). The observations results found 5 types of ectoparasites namely Zoothamnium sp. (2021 ind), Epistylis sp. (955 ind), Carchesium sp. (7 ind), Vorticella sp. (98 ind), and Octolasmis sp. (201 ind).  Organs infected by ectoparasitic are legs (517 ind), swimming legs (476 ind), carapace (740 ind), claws (1348 ind), and gills (201 ind). The highest prevalence rate obtained was Zoothamnium sp. and Epistylis sp. about 95,23% while the lowest prevalence rate was Carchesium sp. about 4,76%. The highest level of intensity was Zoothamnium sp. about 101,05 ind/crab, while the lowest intensity obtained on Carchesium sp. with 7 ind/crab. The condition of water quality was still considered optimal for mud crab (Scylla spp.) life with average temperature of 29,9 ºC, dissolved oxygen 6,6 mg/L, salinity 20‰, and pH 7,39.